2022
DOI: 10.1371/journal.pone.0263589
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of clinical profiles and care for patients with incident versus recurrent acute coronary syndromes in France: Data from the MONICA registries

Abstract: Background Recurrence is common after an acute coronary syndrome (ACS). In order to better assess the prognosis for patients with ACS, we compared clinical profiles, treatments, and case fatality rates for incident vs. recurrent ACS. Methods We enrolled 1,459 men and women (age: 35–74) living in three geographical areas covered by French MONICA registries and who had been admitted to hospital for an ACS in 2015/2016. We recorded and compared the clinical characteristics and medical care for patients with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 26 publications
1
7
1
Order By: Relevance
“…However, our results were lower than the 30% Re-ACS found in the French study ( 25 ). This previous study was conducted on an adult population aged 35–74 years, excluding individuals between the ages of 18 and 35 years.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…However, our results were lower than the 30% Re-ACS found in the French study ( 25 ). This previous study was conducted on an adult population aged 35–74 years, excluding individuals between the ages of 18 and 35 years.…”
Section: Discussioncontrasting
confidence: 96%
“…However, MI that occurs within 28 days of the initial MI event is classified as a case of re-infarction ( 24 ). In this study, recurrent ACS refers to any acute coronary event that occurs after 28 days following the initial incident of ACS ( 25 ). Primary ACS is used to describe ACS that is diagnosed for the first time during the study period.…”
Section: Methodsmentioning
confidence: 99%
“…Relatedly, approximately 15-30% of patients presenting with their first myocardial infarction will be rehospitalized for recurrent cardiac events [103][104][105][106]. Patients hospitalized for recurrent ACS typically have a higher prevalence of diabetes, hyperlipidemia, hypertension, and vascular disease compared to patients experiencing only an incident event [107].…”
Section: Cad Revascularization-challenges With Access Appropriate Use...mentioning
confidence: 99%
“…Patients hospitalized for recurrent ACS typically have a higher prevalence of diabetes, hyperlipidemia, hypertension, and vascular disease compared to patients experiencing only an incident event [107]. They also more often suffer from suboptimal treatment before index hospital admission [106]. Data from the French MONICA population-based registries showed that mortality rates at 28 days (9% vs. 5%, respectively) and one year were higher among recurrent versus incident cases (14% vs. 8%, respectively), independent of age and sex.…”
Section: Cad Revascularization-challenges With Access Appropriate Use...mentioning
confidence: 99%
See 1 more Smart Citation